Allopurinol induces innate immune responses through mitogen‐activated protein kinase signaling pathways in HL‐60 cells. Issue 9 (7th December 2015) - Nakajima, Akira; Oda, Shingo; Yokoi, Tsuyoshi
Abstract: Allopurinol, an inhibitor of xanthine oxidase, is a frequent cause of severe cutaneous adverse reactions (SCARs) in humans, including drug rash with eosinophilia and systemic symptoms, Stevens–Johnson syndrome and toxic epidermal necrolysis. Although SCARs have been suspected to be immune‐mediated, the mechanisms of allopurinol‐induced SCARs remain unclear. In this study, we examined whether allopurinol has the ability to induce innate immune responses in vitro using human dendritic cell (DC)‐like cell lines, including HL‐60, THP‐1 and K562, and a human keratinocyte cell line, HaCaT. In this study, we demonstrate that treatment of HL‐60 cells with allopurinol significantly increased the mRNA expression levels of interleukin‐8, monocyte chemotactic protein‐1 and tumor necrosis factor α in a time‐ and concentration‐dependent manner. Furthermore, allopurinol induced the phosphorylation of mitogen‐activated protein kinases (MAPK), such as c‐Jun N‐terminal kinase and extracellular signal‐regulated kinase, which regulate cytokine production in DC. In addition, allopurinol‐induced increases in cytokine expression were inhibited by co‐treatment with the MAPK inhibitors. Collectively, these results suggest that allopurinol has the ability to induce innate immune responses in a DC‐like cell line through activation of the MAPK signaling pathways. These results indicate that innate immune responses induced by allopurinol might be involved in the development of allopurinol‐induced SCARs. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Allopurinol is a frequent cause of severe cutaneous adverse reactions (SCARs) in humans. Although SCARs have been suspected to be immune‐mediated, the mechanisms of allopurinol‐induced SCARs remain unclear. In this study, we demonstrate that treatment of HL‐60 cells with allopurinol significantly increased the mRNA levels of pro‐inflammatory cytokines, including IL‐8, MCP‐1, and TNFa, through activation of MAPK signaling pathways. These results indicate that innate immune responses induced by allopurinol might be involved in the development of allopurinol‐induced SCARs.